ANALISIS YURIDIS TANGGUNG JAWAB PELATIHAN PEKERJA SWASTA KAJIAN PERBANDINGAN UU NO.13 TAHUN 2003 TENTANG KETENAGAKERJAAN DENGAN UU NO.11TAHUN 2020 TENTANG CIPTA KERJA - Fahruji Hi Jamal; Rumainur (INTELIGENSIA MEDIA, 2023)
Juridical Analysis of Private Worker Training Responsibilities Comparative Study of Law no. 13 of 2003 concerning Employment With Law no. 11 of 2020 concerning Job Creation. The formulation of the problem in this research is: (1) What are the provisions that train private workers in Indonesia? (2) What are the Responsibilities and Obstacles of Implementing Private Worker Training Comparative Study of Law No. 13 of 2003 concerning Manpower and Law No. 11 of 2020 concerning Job Creation.? (3) How Should Private Workers in Indonesia be Trained in the Future Mass?. In this sentence using normative research methods. From the results of research, discussion and analysis it can be concluded that: That the comparison of Law. No. 11 of 2020 concerning Job Creation with the Manpower Law, which then contains several substances that change and delete the substance contained in the Manpower Law. work including regarding government training institutions as referred to in paragraph (1) letter a in organizing job training can cooperate with the private sector. As for the author's suggestion that local governments should prioritize Vocational Training Centers as a forum for handling unemployment rates in all private agencies throughout Indonesia especially in manufacturing companies